(3eSGFd GdEfJbGOs - (3CHj YHO Gddg eMeO Hf SYjO Hf CMeO Hf TQa GdbjQhGfj,J (B460 (3g` s
(3ChdgG (B:s
(3bGd CHhYHOGddg eMeO Hf TQa GdbjQhGfj(B: (3gPg CMGOjK UfYJgG eNJdaI GdCfhGY s
(3BNQgG (B:s
(3hbVi eBQHc, hUai ef GdbPi eTGQHc, hHK aj GdMhGXQ hGdHhGOj efGbHc s
(3eVHhW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B138 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B25s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B57 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdCOHs